Grado de dependencia según Índice de Barthel en pacientes geriátricos hospitalizados en el área de clínica del Hospital Teófilo Dávila de agosto a diciembre del 2011 - Caamaño Solis, Jorge A. (2012)
The objective of this study was to determine the degree of dependence of according to the Barthel index in geriatric patients hospitalized in the area of clinics at Teófilo Dávila Hospital from august to December 2011. The type of study is a cross- sectional and descriptive study, information was obtained conducting a survey to geriatric patients hospitalize in the area of clinic, which contained variables such as age , sex, cause of admission, days of hospitalization and the Barthel index.